Characteristics of 22q 11.2 deletion syndrome undiagnosed until adulthood: an example suggesting the importance of psychiatric manifestations. (8th June 2015) - Furuya, Kenta; Sasaki, Yosuke; Takeuchi, Taizo; Urita, Yoshihisa
Abstract : Patients with chromosome 22q11.2 deletion syndrome (22q11.2DS) exhibit various combinations of signs and symptoms including facial dysmorphism, thymus absence, hypoparathyroidism, cellular immunodeficiency and cardiac abnormalities caused by microdeletion of chromosome 22q11.2. Most cases are diagnosed during post-natal cardiac evaluation, though some are diagnosed at later stages. We report the case of a 39-year-old man with 22q11.2DS presenting with seizure due to tardily manifested hypocalcaemia and anxiety disorder. Our experience suggests that 22q11.2DS patients lacking fatal or well-recognised manifestations such as cardiac defects, immunodeficiency and facial dysmorphism tend to survive without medical attention, and are therefore overlooked. Recognition of the age-related variance of the manifestations, and specifically of tardily manifested hypocalcaemia and psychiatric or developmental disorders as manifestations of 22q11.2DS in adulthood, is important for diagnosis and can also help us provide appropriate medical and psychosocial support for newly diagnosed 22q11.2DS patients in adolescence or adulthood and their families.